Temporary, inconsistent, and null effects of a moral story and instruction on honesty. Issue 1 (15th March 2019) - Sauter, Jessica A.; Stocco, Corey S.; Luczynski, Kevin C.; Moline, Adam D.
Abstract : Lying during childhood is a common concern for caregivers. Lee et al. (2014) showed that a moral story and instruction implying reinforcers for honesty produced statistically significant improvements in children admitting a transgression. We evaluated the influence of this moral story and instruction on the consistency of honest reports when reinforcement favored lying in the context of reporting answers to math problems. The moral story and instruction produced temporary, inconsistent, or null effects across participants. However, reinforcing accurate reports produced consistent improvements in telling the truth.